The use of learning strategies: An international perspective - Gary J. Conti; Rita Kolody (Adult Education Research Conference, 1995)
Learning strategies were examined for students at a post-secondary college in Canada. While some differences were found due to groupings, no distinct patterns were found. A discriminant analysis produced a weak function which was different from previous studies.